2019
DOI: 10.1136/sextrans-2019-054145
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors associated with BV chronicity among women in Rakai, Uganda

Abstract: ObjectivesTo assess risk and protective factors associated with bacterial vaginosis (BV) chronicity ascertained by Nugent score criteria.MethodsA longitudinal cohort study included 255 sexually experienced, postmenarcheal women who provided weekly self-collected vaginal swabs for up to 2 years. Vaginal swabs were scored using Nugent criteria and classified as normal (≤3), intermediate (4–6) and Nugent-BV (≥7). Detailed behavioural/health information were assessed every 6 months. A per-woman longitudinal summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…27 Studies have shown that BV infection is caused by various factors, mainly including microbial diversity of the host vagina, the environment, genetics, and the route of infection. 28,29 In our study, the incidence of BV in the 17-year-old group was the highest among the age groups, which may have been due to vaginal microbial diversity of girls at this age. Additionally, 17-year-old girls in China have a stressful life because of preparation for the College Entrance Examination, with tremendous academic pressure and a lack of exercises.…”
Section: Discussionmentioning
confidence: 53%
“…27 Studies have shown that BV infection is caused by various factors, mainly including microbial diversity of the host vagina, the environment, genetics, and the route of infection. 28,29 In our study, the incidence of BV in the 17-year-old group was the highest among the age groups, which may have been due to vaginal microbial diversity of girls at this age. Additionally, 17-year-old girls in China have a stressful life because of preparation for the College Entrance Examination, with tremendous academic pressure and a lack of exercises.…”
Section: Discussionmentioning
confidence: 53%
“…Surface and spring water are exposed to the environment and may be contaminated by human and animal excreta and other environmental pathogens 36 . Hence, these water sources can be reservoirs of disease‐causing agents resulting in higher likelihood to contribute to infection among users 4–6 . For example, evidence has also shown seasonal outbreaks of waterborne diseases, such as diarrhea, in Bandarban.…”
Section: Discussionmentioning
confidence: 99%
“…36 Hence, these water sources can be reservoirs of disease‐causing agents resulting in higher likelihood to contribute to infection among users. 4 , 5 , 6 For example, evidence has also shown seasonal outbreaks of waterborne diseases, such as diarrhea, in Bandarban. Low level of perceived water quality was negatively associated with any symptom of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation